Akt Phosphorylation at Ser473 Predicts Benefit of Paclitaxel Chemotherapy in Node-Positive Breast Cancer - Yang, Sherry X. (American Society of Clinical Oncology, 2010)
PURPOSE: We tested the hypothesis that Akt-Ser473 phosphorylation (pAkt) predicts benefit from the sequential addition of paclitaxel to adjuvant doxorubicin plus cyclophosphamide (AC) chemotherapy in patients with node-positive breast cancer participating in the National Surgical Adjuvant Breast and Bowel Project (NSABP) B-28 trial. PATIENTS AND METHODS: Primary tumors from the NSABP B-28 trial tissue microarray were available from 1,581 of 3,060 patients who were randomly assigned to receive either four cycles of AC alone or followed by four cycles of paclitaxel. Immunohistochemistry and quantitative analysis of pAkt were performed at the National Cancer Institute blinded to clinical outcome. Association between pAkt and clinical outcome was assessed using multivariate Cox modeling adjusting for age, tumor size, number of positive nodes, tumor grade, estrogen receptor status, and human epidermal growth factor receptor 2 status. RESULTS: With a median follow-up of 9.1 years, there were no differences in disease-free survival (adjusted hazard ratio [HR], 1.02; P = .81) or overall survival (HR, 0.97; P = .80) with and without receiving paclitaxel among 975 patients with pAkt-negative tumors. In 606 patients with pAkt-positive tumors, the sequential addition of paclitaxel resulted in a 26% improvement in disease-free survival (HR, 0.74; P = .02) or a 20% improvement in overall survival (HR, 0.80; P = .17). CONCLUSION: pAkt significantly predicts disease-free benefit from the sequential addition of paclitaxel to AC chemotherapy in patients with node-positive breast cancer. Patients with pAkt-negative breast tumors do not appear to benefit from the addition of paclitaxel.